(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Osteoarthritis (OA) is the most common form of arthritis and is one of the most common degenerative joint diseases in the world. One of its risk factors is related to genetics. The signal from TGF-β, which is mediated by the SMAD3 protein, plays a role in maintaining joint cartilage, so is therefore related to osteoarthritis. The objective of this study is to determine the SMAD3 gene polymorphism rs1065080 in elderly Indonesian patients with grade 4 knee osteoarthritis. Materials and Methods This is a descriptive observational study, with samples taken consecutively from 21 grade 4 knee OA patients. The genome was taken through saliva and isolated using the Quick-DNATM Miniprep Plus Kit from Zymo Research. RT-PCR was then conducted to determine the genotype.Results and Discussion: The SMAD3 rs1065080 gene polymorphism in grade 4 knee OA in the Indonesian elderly patients resulted in the mutant genotype or GG (61.9%), the heterozygous genotype or GA (28.6%), and the normal genotype or AA (9.5%). The G allele (76.2%) was more frequent than the A allele (23.8%). Conclusion The GG genotype and G allele were more frequently found in the study. Analytical studies on larger samples are needed to show the relationship of the SMAD3 rs1065080 gene polymorphism to grade 4 knee OA in Indonesian elderly patients. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 947-952